Dietary Fiber Intake and Femoral Bone Mineral Density in Middle-Aged and Older US Adults: A Cross-Sectional Study of National Health and Nutrition Examination Survey 2013–2014 - Tang, Yuchen; Liu, Jinmin; Zhang, Xiaohui; Geng, Bin (Frontiers in Nutrition, 2022)
Sufficient dietary fiber intake (DFI) is considered necessary for human health. However, the association between bone mineral density (BMD) reminds uncertain. Therefore, this study aimed to investigate the association between DFI and BMD and determine whether the sex modified the association between DFI and BMD. Participants aged ≥ 40 years from the 2013-2014 National Health and Nutrition Examination Survey were included in the final analysis. The association between DFI and BMD was evaluated by the multivariate linear regression models. Moreover, the nonlinear relationship of DFI with BMD was characterized by smooth curve fittings and generalized additive models. Finally, 1,935 participants with 58.12 ± 11.84 years of mean age and 50.96% of the proportion of women were included in the final analysis. The results revealed that DFI was positively associated with femoral BMD in the unadjusted model. However, no correlation was observed between DFI and femoral BMD after adjusting for covariates. For the nonlinear relationship between DFI and femoral BMD, the results showed an inverted U-shaped association between DFI and femoral BMD among males but not females. In addition, DFI was negatively associated with femoral neck BMD (β: -0.0017; 95% CI: -0.0032 to -0.0002) among males when DFI was greater than 25 gm/day. In conclusion, our results indicate that DFI might not follow a linear relationship with femoral BMD, and sex factors might modify the association between DFI and BMD. In particular, high DFI (> 25 gm/day) might contribute to lower femoral neck BMDs among males aged ≥ 40 years. Therefore, more studies are needed to assess the optimal DFI range for middle-aged and older men to prevent bone loss.